Quality evaluation of Polygonatum sibiricum slices from different regions based on appearance traits and multi-index metabolites combined with TOPSIS and gray relation analysis - Wang, Cheng; Ye, Ju; Jiang, Sisi; He, Xuguang; Ma, Min; Yin, Li (Frontiers in Pharmacology, 2025)
IntroductionTraditional Chinese medicine quality control faces challenges, lacking multidimensionality and reliable quantitative evidence. Comprehensive evaluation models based on external characteristics and multiple indicator metabolites are the future research direction. This study focuses on Polygonatum sibiricum slices, aiming to establish a method for its quality evaluation.MethodsThe appearance traits of P. sibiricum slices were quantified, and the contents of six functional metabolites were determined. With eight traits and six metabolite contents as variables, principal component analysis (PCA) and orthogonal partial least-squares discrimination analysis (OPLS-DA) were performed. A weighted TOPSIS-GRA fusion model was established by combining the technique for order preference by similarity to ideal solution (TOPSIS) and gray relation analysis (GRA).ResultsThe six metabolites showed good linear relationships (R2 > 0.9992) within their respective ranges, with an average recovery rate of 98.54% - 103.07% (relative standard deviation less than 1.64%). Precision, stability, and repeatability met the relevant standards. There were significant differences in traits and metabolite contents among slices from different habitats. OPLS-DA identified differential quality-affecting markers. PCA showed that the first three principal components contributed over 80% of the cumulative variance, and 16 batches of slices were clustered into three categories by origin. The weighted TOPSIS-GRA fusion model indicated significant quality differences among slices from different regions, consistent with PCA and OPLS-DA clustering results.DiscussionThe established multi-index content determination method is accurate and reliable for detecting metabolites in P. sibiricum slices. The PCA, OPLS-DA, and weighted TOPSIS-GRA fusion models are scientifically reliable. The correlation between appearance traits and product quality can be used to evaluate P. sibiricum slices from different regions, which is of great significance for quality control and standardization of traditional Chinese medicine.